THE CORRELATION BETWEEN STRESS, SELF-EFFICACY OF PHYSICAL ACTIVITY AND PREDIABETES RISK IN ADULTS AT SAINT THOMAS THE APOSTLE CHURCH BEKASI - Adelheid Melanurista; Dewi Prabawati (Nursing Current: Jurnal Keperawatan, 2022)
Nowadays, changes in lifestyle patterns may cause a lack of physical activity and high-stress level which triggers prediabetes. Some people are unaware that they suffer from prediabetes since no symptoms appear. This study aimed to determine the correlation between the incidence of stress and self-efficacy of physical activity to the risk of prediabetes in Saint Thomas The Apostle Church Bekasi. This research was conducted with a quantitative approach and cross-sectional design. As many as 66 respondents were recruited by purposive sampling technique. The data collection instrument used a Self-Efficacy Exercise (SEE) questionnaire, Perceived Stress Scale (PSS), and Indonesian Prediabetes Risk Score (INA-PRISC) to measure prediabetes. Data analysis used the Kendall Tau-C statistical test. The univariate analysis showed that most respondents had moderate stress (83.3%). In addition, more than half of the respondents had low self-efficacy in physical activity (66.7%), and a very low risk of prediabetes (66.7%).  This study also revealed  a significant correlation between self-efficacy in physical activity and the risk of prediabetes  (p-value o0.030). It is suggested that respondent at Saint Thomas The Apostle Church Bekasi develop a health promotion program assisted by health workers to create a lifestyle pattern regarding good stress management and physical activity self-efficacy to decrease prediabetes risk.